2012
DOI: 10.1063/1.4752108
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of strong ground state electron and hole wave function spatial overlap in nonpolar GaN/AlN quantum dots

Abstract: We present a detailed analysis of the electrostatic built-in field, the electronic structure, and the optical properties of a-plane GaN/AlN quantum dots with an arrowhead-shaped geometry. This geometry is based on extensive experimental analysis given in the literature. Our results indicate that the spatial overlap of electron and hole ground state wave functions is significantly increased, compared to that of a c-plane system, when taking the experimentally suggested trapezoid-shaped dot base into account. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This puts forward the need for other mechanisms that should account for additional reductions of the internal electric fields in non-polar QDs. While some authors have demonstrated that the shape of the dots [13] or the presence of free carriers [20] can increase the oscillator strength of the transitions or screen builtin electric fields, no attention has been paid to the existence of structural defects, such as BSFs, revealed in the PL spectra of Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This puts forward the need for other mechanisms that should account for additional reductions of the internal electric fields in non-polar QDs. While some authors have demonstrated that the shape of the dots [13] or the presence of free carriers [20] can increase the oscillator strength of the transitions or screen builtin electric fields, no attention has been paid to the existence of structural defects, such as BSFs, revealed in the PL spectra of Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis is simplified by taking the same elastic constant values in the dot and matrix, which is a good approximation for GaN and AlN. Since the shape of the non-polar QDs can be crucial for their optical properties [13], we turn to the Fourier space where it is always possible to obtain the analytical solutions forũ i (q) for any QD shape. Finally, the built-in electrostatic potential is computed considering the spontaneous, P sp = (0, 0, P sp z ), and piezoelectric, P pz = (P pz x , P pz y , P pz z ), contributions for the total material polarization.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Status Solidi B 252, No. 10 (2015) 2297 order to accurately model their optical properties [10]. The shape of the QDs is critical and more important when QDs of approximately same volume are being compared due to the change the different shapes induces in the electrostatic potential within the QDs [10].…”
Section: Papermentioning
confidence: 99%
“…A detailed analysis of the built‐in potential and electronic structure of that system was presented in (), where suppression of the electric field was reported for the nonpolar case. Moreover, it was found that the precise geometry of the QDs and also the Coulomb interactions between charge carriers have to be taken into consideration in order to accurately model their optical properties (). The shape of the QDs is critical and more important when QDs of approximately same volume are being compared due to the change the different shapes induces in the electrostatic potential within the QDs ().…”
Section: Introductionmentioning
confidence: 99%